The Influence Of Service Facilities, Innovation, And Product Knowledge On Passenger Satisfaction In Using Self Check-In Kiosks At Adi Soemarmo Boyolali International Airport - Ema Susanti; Ida Aryati DPW; Bambang Mursito (JURNAL ILMIAH EDUNOMIKA, 2023)
The study's goal was to learn more about service facilities, innovation, and product knowledge on passenger satisfaction in using self check-in kiosks at the international airport of Adi Soemarmo. Quantitative techniques are used in the research design. Multiple linear regressions were used to examine research data. The sample consisted of 100 Lion Air Group passenger respondents who checked-in using a self check-in kiosk. The results showed that service facilities, product innovation and product knowledge in the use of self check-in at Adi Soemarmo International Airport significantly influence passenger satisfaction. . Keywords : Service Facility, Product Innovation, Product Knowledge, Self Check-in Kiosk